Conceptions of Freedom, Justice and Equality in the current Chilean labour reform debate. A discourse analysis - Martin, Angel; Ravest, Javiera (Revista Némesis, 2016)
Among the priorities of the New Majority's government programme is a labour agenda aimed at modernising labour relations, in response to the democratic deficit and the growing precariousness of employment generated by the Labour Plan inherited from the authoritarian period. In 2015, criticism of the bill was not slow in coming, curiously from the most diverse political and social spectrum: political parties and organisations, business associations and trade unions, as well as a considerable part of the academic and intellectual world, highlighting the inadequacies of the labour reform still being processed. Despite the divergent origins of the criticisms of the reform, all of them appeal in their discourse to Equality, Freedom and Justice as inalienable values. How can we understand what particular conception of each of these concepts the participants in the debate are referring to? This article presents the results of the discourse analysis that explores the uses of the aforementioned conceptual triad, learning about their ideological underpinnings and the similarities and differences between the social and political organisations studied.